Training: Priority Analysis of Health Problems and Activity Intervention Priorities for Village Apparatus in the Work Area of the Benteng Health Center - Akhiat, Akhiat (Journal of Drug Delivery and Therapeutics, 2022)
Establishing Priorities in population health issues and determining priorities in the intervention programs implemented are important given the limitations of HR and financial resources. Health problems must be addressed inclusively, that is, together with relevant agencies. This study aims to look at the effect of health education on prioritizing health issues and their interventions on the knowledge of village officials. This research was conducted in Pangkalan Baru District. The research sample used was 30 people. The method used is pre-experimental design with one group pre-test post-test design. Data collection using a questionnaire. The data analysis technique uses the Wilcoxon technique. The results showed that the knowledge of the Village Apparatus before being given health education with an average value of 74.21 and after being given health education became 91.3%. Hypothesis test results with an error rate of 0.05 obtained p value <0.05 means that there are significant differences from the knowledge of the Village Apparatus after and before the training Keywords: Health, Problem, Intervention